History and Main Content of the Competency Approach - Dustkabilovich, Rakhimov Oktyabr; Munisa, Cho‘lieva (Lembaga Yasin AlSys, 2025)
This article examines the importance and necessity of determining personnel competence in modern production conditions and elucidates the essence and content of the competency approach, including the history of its emergence. It highlights the coexistence of American and European definitions of competence, with particular emphasis on the American concept. The article analyzes the research findings of David McClelland and Richard Boyatzis that aim to define the content of competence in terms of theoretical knowledge, experience, personal characteristics, and abilities.